2015
DOI: 10.1093/jxb/erv463
|View full text |Cite
|
Sign up to set email alerts
|

Sustained enhancement of photosynthesis in coffee trees grown under free-air CO2enrichment conditions: disentangling the contributions of stomatal, mesophyll, and biochemical limitations

Abstract: HighlightIn free-air CO2 enrichment (FACE)-grown coffee trees, elevated [CO2] led to sustained increases in photosynthesis, with no change in mesophyll or stomatal conductance and no downregulation of biochemical capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 55 publications
(90 reference statements)
8
63
1
8
Order By: Relevance
“…The factors limiting photosynthesis are usually attributed to restriction of CO 2 conductance from the atmosphere to the carboxylation site and restriction of CO 2 assimilation in chloroplast stroma under saturating light conditions (Niinemets et al , Warren ). CO 2 conductance includes stomatal conductance ( g s ) and mesophyll conductance ( g m ) (Grassi and Magnani , DaMatta et al ). Increasing leaf N content is beneficial for increasing g s and g m and stimulating CO 2 conductance (Xiong et al ).…”
Section: Introductionmentioning
confidence: 99%
“…The factors limiting photosynthesis are usually attributed to restriction of CO 2 conductance from the atmosphere to the carboxylation site and restriction of CO 2 assimilation in chloroplast stroma under saturating light conditions (Niinemets et al , Warren ). CO 2 conductance includes stomatal conductance ( g s ) and mesophyll conductance ( g m ) (Grassi and Magnani , DaMatta et al ). Increasing leaf N content is beneficial for increasing g s and g m and stimulating CO 2 conductance (Xiong et al ).…”
Section: Introductionmentioning
confidence: 99%
“…As duas cultivares apresentaram maior área foliar e taxa de crescimento em altura e em diâmetro do caule, quando cultivadas em ambiente com adição de CO 2 . O aumento do desenvolvimento de plantas foi observado por outros autores e é resultante do estímulo à fotossíntese (Ramalho et al, 2013;Ghini et al, 2015;DaMatta et al, 2016). Carvalho et al (2010) relataram que há correlação positiva entre altura de plantas, diâmetro do caule e produtividade do café, o que ressalta a importância de estudos que abordem o efeito do aumento do CO 2 do ar na cultura.…”
Section: Resultsunclassified
“…As estufas de topo aberto (OTCs, open top chambers) têm sido utilizadas para a avaliação do impacto do aumento da concentração de gases em diversos países (Pritchard & Amthor, 2005;Lessin & Ghini, 2009 Os trabalhos sobre os impactos do aumento da concentração de CO 2 atmosférico sobre a cultura do café, em geral, abordam efeitos sobre a fisiologia das plantas (Ramalho et al, 2013;Batista, 2015;Ghini et al, 2015;DaMatta et al, 2016), em que aspectos fitossanitários foram pouco estudados. O CO 2 à alta concentração estimula a fotossíntese e o crescimento das plantas.…”
Section: Introductionunclassified
“…Downregulation of photosynthesis has been associated with NSC accumulation in C. arabica (e.g., starch in DaMatta, Maestri, Mosquim, and Barros (1997), sucrose in Franck et al., 2006), while other studies have found no link between NSC and photosynthetic downregulation (Batista et al., 2011; DaMatta et al., 2016; Silva et al., 2004). In contrast, we found a positive relationship between starch and photosynthesis in controls and the 45‐min group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Given that even short heat events can have substantial impacts on carbon gain (Filewod & Thomas, 2014), the predicted fluctuations in the duration of summer heat waves (Della-Marta, Haylock, Luterbacher, & Wanner, 2007), and the paucity of studies manipulating heat stress duration, research on the effects of heat stress duration on physiological recovery and NSC dynamics is needed. NSC dynamics in C. arabica are tightly linked to sink demand from vegetative and reproductive growth (Chaves, Martins, Batista, Celin, & DaMatta, 2012;Génard et al, 2008;Ramalho et al, 2013), and many studies have investigated whether NSC levels regulate C. arabica photosynthesis (Batista et al, 2011;DaMatta et al, 2016;Franck, Vaast, Génard, & Dauzat, 2006;Ronchi et al, 2006;Vaast, Angrand, Franck, Dauzat, & Génard, 2005).…”
Section: Introductionmentioning
confidence: 99%